The Economics of Soviet Merchant-Shipping Policy - Athay, Robert E. (Chapel Hill: University of North Carolina Press, 1971)
During the past decade, the Soviet Union has assumed a major role in world ocean shipping. This development has produced concern and even anxiety in the Western world, particularly among individuals and groups involved in merchant shipping. As a consequence, this study is mainly to evaluate the contribution of Soviet shipping policy to the country's broader economic objectives.
Bibliography: p. 139-144.
ne 22/02/2018
Loan
Keywords: Merchant Marine; Soviet Union